Plainly wrong - Perry, A (Wiley, 2022)
English law and wider common law jurisprudence have endorsed the condition that an appellate court should reject a trial judge's finding of fact which it believes is “plainly wrong”. Courts have not explained what makes a finding plainly wrong, however. Scholars have largely ignored the issue. This article draws on recent work in epistemology to provide a new analysis of the plainly wrong standard. Rationally, a court should not believe both (1) that a judge is a better fact finder and (2) that the judge was wrong to find some fact. If it does believe both, it should abandon the belief it is less confident of. So, a court should reject a judge's finding if it is more confident that it is wrong than that the judge is a better fact finder. This analysis has implications for review of administrative fact finding and for judicial deference generally.